The Social Security System, the Provision of Human Capital, and the Structure of Compensation - Black, Dan A. (Journal of Labor Economics, 1987)
In this paper I examine the effect of the current social security system on the structure of compensation that a wealth-maximizing worker selects. I show that the current method of benefit determination encourages an upward-sloping wage profile and that the social security system alters the mix of wage and pension payments. In addition, the intragenerational transfers of the social security system alter the level of investment in human capital. As a result, the social security system reduces the disparity of income within the economy.